Autonomous sailboats: an emerging technology for ocean sampling and surveillance - Nuno A. Cruz (2008)
Autonomous sailboats are robotic vessels that use wind energy for propulsion and control the sails and rudders without human intervention. The use of autonomous sailboats for ocean sampling has been tentatively proposed before, but there have been minor efforts towards the development and deployment of actual prototypes, due to a number of technical limitations and significant risks of operation. Currently, most of the limitations have been surpassed, with the availability of extremely low power electronics, flexible computational systems, reliable communication devices and high performance renewable power sources. At the same time, some of the major risks have been mitigated, allowing this emerging technology to become an effective tool for a wide range of applications in real scenarios. We illustrate some of these scenarios and we describe the status of the current efforts being made to develop operational prototypes.